Treatment of Recurrent Undifferentiated Pleomorphic Sarcoma of Infratemporal Fossa by Surgery Combined With Carbon Ion Radiotherapy: One Case Report - Wang, Zaixing; Tang, Zhiyuan; Zhao, Hailiang; Zeng, Xianhai; Han, Xiaodong; Zhang, Qiuhang (Frontiers in Surgery, 2021)
We retrospectively analyzed the diagnosis and treatment process of one patient with recurrent undifferentiated pleomorphic sarcoma (UPS) of infratemporal fossa and made a definite diagnosis by combining the imaging and pathological examination results. After treatment failure with 2 cycles of chemotherapy and several surgeries, UPS was eventually treated by surgery + carbon ion radiotherapy, and MRI reexamination showed no relapse. Head & neck UPS is located deeply, easily recurs after operation, and difficult to be resected completely by surgery, with a gradually shortened interval of relapse over the number of surgeries, which becomes a treatment challenge. After the last surgery, the patient received carbon ion radiotherapy, with a good therapeutic effect, and no sign of relapse just before sending this article. Based on the above advantages, we have concluded that surgery + carbon ion radiotherapy is a new effective pathway to treat head & neck UPS. Highlight： 1.Surgical excision of UPS alone cannot achieve the goal of cure. 2.The UPS of head and neck region is not sensitive to chemotherapy. 3.The UPS could be controlled and cured by operation with carbon-ion radiotherapy,However, long-term efficacy remains to be seen.